Social Media Wise Training as an Effort to Develop Character in the Community in Rajabasa Lama Village - Muhammad Nurwahidin; Muhisom Muhisom; Dayu Rika Perdana; Amrina Izzatika; Resti Apriliyani (Budapest International Research and Critics University, 2023)
In the era of rapidly developing technology, playing social media has become a routine for the society. The world seems to be turning digital. Humans always need interaction and interaction requires certain ways. The most used means of interaction today is social media. Social media is one of the most exciting activities online today, but, social media also has an impact on its users, both positive and negative impacts. The positive impact of social media can add insight and meet many people. But behind that there are negative impacts related to social media abuse. This study aims to find out what are the impacts of social media and how important social media is for character education and the importance of holding a training entitled